Composition of the organic matter of sediments from the Kuril-Kamchatka Trench. - Romankevich, Evgeny A (PANGAEA, 1969)
From results of analyses of sediment samples collected on a profile crossing the Kuril-Kamchatka Trench distribution of organic D, N. carbohydrates, lipids and humic substances was established, as well as nature of their relationship with amorphous silica and clay fraction. Sum of the main biochemical groups of organic matter in the surface layer of sediments (0-1 cm) from the Kuril-Kamchatka Trench amounts to about 15%; neogenetic forms not encountered in living organisms make up 85% of organic matter. Among such forms 26% comprise humic substances formed during initial stages of polymerization of decomposition products of biochemical macromolecules.
(Table 1) Composition of organic matter in bottom sediments from the Kuril-Kamchatka Trench
Keywords: Archive of Ocean Data; ARCOD; Carbohydrates; Carbohydrates, total; Carbon, organic, total; Carbon/Nitrogen ratio; DEPTH, sediment/rock; Grab; GRAB; Humic acids; JUDAY; Juday net; Kuril-Kamchatka Trench; Lipids; Lipids, total; Nitrogen, organic; Nitrogen, total; Northwest Pacific; Organic matter; Sediment type; VITYAZ; Vityaz (ex-Mars); VITYAZ5603-GR; VITYAZ5608-GR; VITYAZ5612-GR; VITYAZ5617; VITYAZ5620-GR; VITYAZ5622-GR